Analysis and development of numerical methodologies for simulation of flow control with dielectric barrier discharge actuators - Abdollahzadehsangroudi, Mohammadmahdi (2014)
The aim of this thesis is to investigate and develop different numerical methodologies for modeling the Dielectric Barrier discharge (DBD) plasma actuators for flow control purposes. Two different modeling approaches were considered; one based on Plasma-fluid model and the other based on a phenomenological model. A three component Plasma fluid model based on the transport equations of charged particles was implemented in this thesis in OpenFOAM, using several techniques to reduce the numerical issues. The coupled plasma-fluid problem involves wide range of length and time scales which make the numerical simulation difficult. Therefore, to obtain stable and accurate results in a reasonable computational run time, several numerical procedures were implemented including: semi-implicit treatment of coupling of Poisson equation and charge density equation, super-time-stepping and operator splitting algorithm. We examined our code for a constant positive voltage, testing for the dependency of the behavior of the current density to the selected numerical scheme. In addition, although there is no clear numerical or experimental benchmark case for DBD plasma actuator problem, the developed plasma solver was compared quantitively and qualitively with several numerical works in the literature. Afterward, the developed numerical methodology was used to explore the possibility of influencing the flow, with higher speed, using nano-second (NS) pulsed DBD plasma actuator. Therefore, the interaction of the transonic flow and actuation effects of DBD plasma actuator with nano second pulsed voltage was simulated. The effect of gas heating and body force was calculated by the plasma solver and was supplied into the gas dynamic solver for simulating the flow field. Moreover, the results of the plasma fluid model were used to develop an energy deposition model. It was shown that the energy deposition model is able to capture the main features of the effect of NS DBD plasma actuators correctly, with less computational time. It was also shown that fast energy transfer, from plasma to fluid, leads to the formation of micro-shock waves that modify locally the features of the transonic flow. Although the numerical efficiency of the plasma fluid model was improved, the computational cost of simulating the effect of DBD plasma actuator on a real scale flow situation was still high. Therefore, a simple model for plasma discharge and its effect on the flow was developed based on scaling of the thrust generated by DBD plasma actuators. The scaled thrust model correctly predicts the nonlinear dependency of the thrust produced and the applied voltage. These scales were then introduced into a simple phenomenological model to estimate and simulate the body force distribution generated by the plasma actuator. Although the model includes some experimental correlations, it does not need any fitting parameter. The model was validated with experimental results and showed better accuracy compared to previous plasma models. Using a simple phenomenological model that was developed here, a numerical study was conducted to investigate and compare the effect of steady and unsteady actuation for controlling the flow at relatively high Reynolds number. Firstly it was shown that the size of the time-averaged separation bubble is greatly reduced and the flow structure is sensitive to the frequency of burst modulation of DBD plasma actuators. The results also confirmed that in the case of unsteady actuation, the burst frequency and burst ratio are crucial parameters for influencing the capability of the actuators to control the flow. It was found that burst frequencies near the natural frequencies of the system were able to excite the flow structure in a resonance mode. This observation also confirmed that with proper frequencies of excitation, the flow structure can be well rearranged and the flow losses can be reduced. In the end, Plasma actuators were used for controlling the flow over the Coanda surface of the ACHEON nozzle. When the plasma actuator was used, it was possible to postpone separation of the flow and increase the deflection angle of the exit jet of the nozzle. To find the optimum position of the actuators, seven DBD actuators in forward forcing mode were placed over the Coanda surface considering the numerically obtained separation points. Results show that when the actuator is placed slightly before the separation point, enhanced thrust vectorizing with the use of DBD actuator is achievable. Preliminary results of the experiments agree with planned/foreseen deflection angle obtained from numerical computation.